Microfinance Industry in Bangladesh and India: International Perspectives - Saeed, M. (Gyan Management Journal, 2012)
The study explores the micro.finance industry in Bangladesh and India. Grameen Bank proved th financial inclusion of low-income households is the way out of poverty and that lending to poor can profitable to both the borrower as well as the lender. Since then many micro.finance institutions ca up either following the same operating model as Grameen Bank or some form of its derivative. Ma micro.finance institutions (MF!s) in lndia started as non-profit NGOs and soon became for-profit n banking financial companies (NBFCs) reflecting the financial viability of these institutions. With h. returns, promising growth and portfolio diversification capabilities, micro.finance industry in India become a hotspot for foreign as well as local investors. Apart from widely known benefits, the study highlights the criticism and challenges faced by the micro.finance industry worldwide.